2021
DOI: 10.1002/vms3.556
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate peel as a phytogenic in broiler chickens: Influence upon antioxidant, lipogenesis and hypotensive response

Abstract: The aim of this study was to evaluate antioxidant, antihyperlipidemic and hypotensive properties of pomegranate peel (PP) on antioxidant status, fat deposition, lipid peroxidation and pulmonary hypertensive response in broiler chickens. A total of 375 one‐day‐old male broilers (Cobb 500) were randomly assigned to five treatments included dietary PP levels of 0, 2.5, 5.0, 7.5 and 10 g/kg. Supplementation of PP at 7.5 and 10 g/kg resulted in significant upregulation of hepatic catalase (p < 0.004) and superoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Normally, fewer free radicals are produced of poultry, which can be timely eliminated by the antioxidant system to prevent oxidative stress and injury (1). However, with the increase in poultry production scale and intensity, various factors, such as excessive feeding, lower feeding management, unstable feed quality (excessive metal element content, mycotoxin pollution, and lipid oxidation), and pathogen infestation increase the free radical production in poultry through the respiratory burst mechanism, which exceeds the scavenging capacity of the antioxidant system, triggering a free radical chain reaction, which leads to oxidative stress, and damage (2)(3)(4)(5)(6)(7). In chicks, oxidative stress also reduces disease resistance, survival rate, feed return, and production performance and causes maldevelopment.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, fewer free radicals are produced of poultry, which can be timely eliminated by the antioxidant system to prevent oxidative stress and injury (1). However, with the increase in poultry production scale and intensity, various factors, such as excessive feeding, lower feeding management, unstable feed quality (excessive metal element content, mycotoxin pollution, and lipid oxidation), and pathogen infestation increase the free radical production in poultry through the respiratory burst mechanism, which exceeds the scavenging capacity of the antioxidant system, triggering a free radical chain reaction, which leads to oxidative stress, and damage (2)(3)(4)(5)(6)(7). In chicks, oxidative stress also reduces disease resistance, survival rate, feed return, and production performance and causes maldevelopment.…”
Section: Introductionmentioning
confidence: 99%
“…Pomegranate is a rich source of flavonoids, with the peel containing the highest flavonoid content and greatest antioxidant capacity compared to the seed and juice (Rafiei and Khajali, 2021). Feeding broiler chickens with pomegranate peel at 7.5 and 10 g/kg effectively subsided right ventricular hypertrophy and decreased ascites mortality (Ahmadipour et al., 2021). Inclusion of 5 g/kg garlic bulb in diets effectively reduced ascites incidence in broiler chickens (Varmaghany et al., 2015).…”
Section: Nutritional Strategies At High Altitudementioning
confidence: 99%
“…Numerous biological activities have been attributed to PP, such as antioxidant, antitumor, anti-infammatory, neuroprotective, antiviral, and antibacterial efects [3]. Ahmadipour et al found that PP reduced pulmonary hypertension and blood pressure in broiler chickens due to its antioxidant and hypolipidemic efects [4] and it was also shown to reduce serum malondialdehyde in broilers [5]. Te phenolic and favonoid compounds present in PP scavenged reactive oxygen species to produce antihyperglycemic and antihyperlipidemic actions.…”
Section: Introductionmentioning
confidence: 99%